Spectrophotometric Determination of Ezetimibe - P. Baby Sudha Lakshmi; D. Ramchandran; C. Rambabu (E-Journal of Chemistry)
Two simple, sensitive, selective and accurate spectro-photometric methods (Method A and Method B) for the determination of eztimibe in bulk drug and pharmaceutical formulations (tablets) have been described. Method A and B are based on the redox/complex formation reaction of drug with 1,10-phenanthroline and hexacyano-ferrate(III) in presence of ferric chloride to form coloured chromogens exhibiting λmax at 510 and 740 nm respectively. The results of analysis for the two methods have been validated statistically and by recovery studies. The results are compared with those obtained using UV spectrophotometric method in alcohol at 231.7 nm.